Dragonfly Species Diversity in Lembang Mokallang Village, Mamasa Regency, West Sulawesi, Indonesia - Hadris; Andi Dewi Rizka Ainulia Makerra; Muh Anas (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2024)
This study aimed to determine the diversity index of dragonfly species. Observations were conducted using the capture–recapture method, which involved capturing dragonflies, marking them, and releasing them back into their habitat. The recording of each dragonfly species was carried out using an exploration method by surveying specific areas and recording and counting the number of individuals of each species encountered. The study was conducted in August 2023 at three research stations. Data analysis was performed using the Shannon–Wiener diversity index (H’). The data were analyzed using the PAST (Paleontological Statistics) application. The results showed that a total of 11 species with 539 individuals belonging to four families were recorded. The most abundant species was Pantala flavescens, with 113 individuals. The diversity index values were H’ = 1.993 at Station I, H’ = 1.739 at Station II, and H’ = 1.937 at Station III. Overall, the dragonfly diversity index at each station in Lembang Mokallang Village, Mamasa Regency, was categorized as moderate diversity